Expression of the Maize Dof1 Transcription Factor in Wheat and Sorghum - Peña, Pamela A.; Quach, Truyen; Sato, Shirley; Ge, Zhengxiang; Nersesian, Natalya; Changa, Taity; Dweikat, Ismail; Soundararajan, Madhavan; Clemente, Tom E. (Frontiers in Plant Science, 2017)
Nitrogen is essential for plant growth and development. Improving the ability of plants to acquire and assimilate nitrogen more efficiently is a key agronomic parameter that will augment sustainability in agriculture. A transcription factor approach was pursued to address improvement of nitrogen use efficiency in two major commodity crops. To this end, the Zea mays Dof1 (ZmDof1) transcription factor was expressed in both wheat (Triticum aestivum) and sorghum (Sorghum bicolor) either constitutively, UBI4 promoter from sugarcane, or in a tissue specific fashion via the maize rbcS1 promoter. The primary transcription activation target of ZmDof1, phosphoenolpyruvate carboxylase (PEPC), is observed in transgenic wheat events. Expression ZmDof1 under control of the rbcs1 promoter translates to increase in biomass and yield components in wheat. However, constitutive expression of ZmDof1 led to the down-regulation of genes involved in photosynthesis and the functional apparatus of chloroplasts, and an outcome that negatively impacts photosynthesis, height and biomass in wheat. Similar patterns were also observed in sorghum transgenic events harboring the constitutive expression cassette of ZmDof1. These results indicate that transcription factor strategies to boost agronomic phenotypic outcomes in crops need to consider expression patterns of the genetic elements to be introduced.